Corporate Funding and the COVID-19 Crisis - Deghi, Andrea (IMF Working Papers; Working Paper ;, 2021)
This paper assesses whether corporate liquidity needs in the G7 economies were met during the containment phase of the COVID-19 pandemic (February-June 2020) using various approaches to identify credit supply shocks. The pandemic crisis adversely affected nonfinancial corporate sector cash flows, generating liquidity and solvency pressures. However, corporate borrowing surged in March and into the second quarter, thanks to credit line drawdowns and unprecedented policy support. In the United States, the bond market was buoyant from the end of March onward, but credit supply conditions for bank loans and the syndicated loan market tightened. In other G7 economies, credit supply conditions generally eased somewhat across markets during the second quarter. Among listed firms, entities with weaker liquidity or solvency positions before the onset of COVID-19, as well as smaller firms, suffered relatively more financial stress in some economies in the early stages of the crisis. Residual signs of strain remained as of the end of June. Policy interventions, especially those directly targeting the corporate sector, had a beneficial effect on credit supply overall.